The Diagnostic Dilemma of Charcot Foot in 73 Year-Old-Female - Helena, Helena; Rosandi, Rulli (Universitas Brawijaya, 2020)
Charcot neuroarthropathy (CN) is a progressive degenerative arthropathy of weight-bearing joints, which rarely complicates diabetes mellitus, usually in the foot or ankle. Commonly, when affecting the foot, it seems to be determined by the interaction of neuropathy, osteopenia, and proinflammatory cytokines on a calcified peripheral vasculature that maintains its ability to vasodilate despite widespread arteriosclerosis. Although often unrecalled, this arthropathy is probably triggered by trauma. Diagnosis is primarily clinical, given the lack and non-specificity of radiological and biochemical findings at the acute stage. CN should be considered in the differential diagnosis of any diabetic patient presenting with a warm swollen lower extremity. Offloading is essential and improves limb survival. Failure to institute corrective measures at an early stage results in a foot that is prone to deformity, ulceration, amputation, and loss of function. We report a case of Charcot foot in a 73 years old female and review of diagnostic modalities.